Unusual gait disorders: a phenomenological approach and classification. (1st February 2019) - Paramanandam, Vijayashankar; Lizarraga, Karlo J.; Soh, Derrick; Algarni, Musleh; Rohani, Mohammad; Fasano, Alfonso
ABSTRACT: Introduction : Gait impairment is a very common problem in clinical practice. Multiple classifications of gait disorders are available based on anatomy, etiology, pathology and phenomenology. These classifications provide a diagnostic guide but do not clearly explain the pathophysiology of some gait disorders, which can sometimes hinder the diagnostic process. In this context, unusual gait disorders become an even more difficult clinical challenge. Areas covered : The scientific and non-scientific literature contains illustrative descriptions of unusual gait disorders based on their predominant signs and/or comparisons with normal and abnormal zoological and folkloric patterns. Unusual gait disorder phenomenology can be carefully deconstructed in order to achieve an integral approach. We present a pragmatic, phenomenological approach to various unusual gait disorders and highlight key features underlying their phenotypes. We also propose unifying terminology to facilitate diagnosis and academic communication. Expert commentary : Advanced gait analysis, neurophysiological and neuroimaging techniques have allowed for us to recognize that locomotion is a complex motor behavior that requires simultaneous integration of multiple neurological and non-neurological systems. A phenomenological approach such as the one proposed in this review could be useful while those objective techniques become more widely available in clinical practice.